IMPLEMENTING ORGANIZATIONAL SKILLS IN THE CLASSROOM - Marisi Debora (BAHAS, 2015)
This article presents the writer’s experience in the classroom in implementing the organizational skills. The article also discuss the reason for teaching organizational skills in the classroom, materials needed for the teaching and the implementation of the organizational skills in the classroom. The materials can be adjusted to the availability in the class and the students’ own stationery. The two stages of implementation later build the students’ independence which is the goal of teaching and preparing them for successful academic life.   Key Words: organizational skills, teaching organizational skills, implementing